Ion-Transfer Voltammetric Determination of the B-Blocker Propranolol in a Physiological Matrix at Silicon Membrane-Based Liquid/Liquid Microinterface Arrays - Collins, C.; Arrigan, Damien (American Chemical Society, 2009)
In this work, the ion-transfer voltammetric detection ofthe protonated -blocker propranolol in artificial saliva ispresented. Cyclic voltammetry, differential pulse voltammetry,and differential pulse stripping voltammetry (DPSV)were employed in the detection of the cationic drug basedon ion-transfer voltammetry across arrays of microinterfacesbetween artificial saliva and an organogel phase. Itwas found that the artificial saliva matrix decreased theavailable potential window for ion-transfer voltammetryat this liquid|liquid interface but transfer of protonatedpropranolol was still achieved. The DPSV method employeda preconditioning step as well as a preconcentrationstep followed by analytical signal generation basedon the back-transfer of the drug across the array ofmicrointerfaces. The DPSV peak current response waslinear with drug concentration in the artificial saliva matrixover the concentration range of 0.05-1 µM (ip ) -8.13(nA µM-1)(concentration) + 0.07 (nA), R ) 0.9929,n ) 7), and the calculated detection limit (3sb) was0.02 µM. These results demonstrate that DPSV atarrays of liquid|liquid microinterfaces is a viable analyticalapproach for pharmaceutical determinations inbiomimetic matrixes.